Deep Spitzer observations of infrared-faint radio sources: High-redshift radio-loud active galactic nuclei? - Norris, R.; Afonso, J.; Cava, A.; Farrah, D.; Huynh, M.; Ivison, R.; Jarvis, M.; Lacy, M.; Mao, M.; Maraston, C.; Mauduit, J.; Middelberg, E.; et al. (2011)
Infrared-faint radio sources (IFRSs) are a rare class of objects which are relatively bright at radio wavelengths but very faint at infrared and optical wavelengths. Here we present sensitive near-infrared observations of a sample of these sources taken as part of the Spitzer Extragalactic Representative Volume Survey. Nearly all the IFRSs are undetected at a level of ~1 µJy in these new deep observations, and even the detections are consistent with confusion with unrelated galaxies. A stacked image implies that the median flux density is S3.6 µm ~ 0.2 µJy or less, giving extreme values of the radio-infrared flux density ratio. Comparison of these objects with known classes of object suggests that the majority are probably high-redshift radio-loud galaxies, possibly suffering from significant dust extinction. © 2011. The American Astronomical Society. All rights reserved.